Konstruksi Diskresi Jaksa dalam Penghentian Penuntutan Berdasarkan Keadilan Restoratif: Studi Grounded Theory pada Perkara Pidana Umum - Maulana Fahmi Idris; Sri Yulianingsih; Poppy Fitrijanti Soeparan (Universitas Sains dan Teknologi Komputer, 2026)
This study aims to develop a substantive theory explaining the construction of prosecutorial discretion in the termination of prosecution under restorative justice in Indonesia. Although restorative justice has increasingly been incorporated into contemporary criminal justice systems, the mechanisms through which prosecutors construct and legitimize decisions to discontinue prosecution remain insufficiently understood. Using a grounded theory approach, data were collected through in-depth interviews, document analysis, and theoretical sampling. Data analysis was conducted through iterative stages of initial coding, focused coding, and theoretical coding until theoretical saturation was achieved. The findings reveal that prosecutorial discretion does not operate as a linear administrative procedure but rather as a dynamic and recursive multi-rationality causal system. The study develops a theoretical model termed the Structured Tension–Based Restorative Rationality Mechanism (ST-RRM) , which explains that prosecutorial decisions emerge through the interaction of legal thresholds, restorative validation, relational legitimacy, institutional constraints, and prosecutorial professional identity. The findings indicate that restorative rationality becomes the dominant decision-making logic when three key conditions are simultaneously satisfied: legal eligibility, socially validated victim restoration, and relational legitimacy. Nevertheless, the decision-making process remains embedded within structural constraints, allowing outcomes to be continuously reassessed through institutional and social feedback mechanisms. This study contributes to the literature on prosecutorial discretion by introducing a multi-rationality structured tension theory , conceptualizing discretion as a socio-institutional construction process that integrates legal certainty, victim restoration, and social legitimacy within an adaptive decision-making system.